Sintesis dan Karakterisasi Enkapsulat Katalis Nikel (II) pada Silika Mesopori Modifikasi - Admi, Admi; Ramadhani, Fitria; Syukri, Syukri (Jurnal Riset Kimia, 2020)
Ni(II)-BF3/MCM-41 was synthesized for heterogeneous catalyst. The boron trifluoride modified mesoporous silica BF3/MCM-41 was studied to investigate its ability as supporting agent in heterogeneous catalysis system. For this purpose, the structural directing agent remaining in as-synthesis MCM-41 removed by solvent extraction. Surface modification of mesoporous silica MCM-41 with aniline and boron trifluoride was carried out. Then, the surface of boron trifluoride modified mesoporous silica was subjected to an encapsulation with Ni(II) ions. These solid materials were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and atomic absorption spectroscopy (AAS). In the FTIR spectra of the modified silica mesoporous, the presence of vibration band >Si-O-B confirm the success of modification of support. While, the shifting of the vibration band >Si-O-Si< is considered an indication of the proof of Ni(II) species onto the modified mesoporous silica. From the SEM photograph, it can be seen that the morphology of the Ni(II)-BF3/MCM-41 tend to form aggregates of smaller particles. Based on measurement of metal content by AAS, it was known that the value of metal loading is 33%. While for the leaching test, Ni(II)-BF3/MCM-41 lost only 0.014 % of Ni metal. It indicates the stability of the interaction between the N(II) and support of the modified mesoporous silica.